1997
DOI: 10.1128/aac.41.4.869
|View full text |Cite
|
Sign up to set email alerts
|

Active efflux of antimicrobial agents in wild-type strains of enterococci

Abstract: Enterococci are intrinsically resistant to numerous antimicrobial agents. We examined the energy-dependent efflux of radiolabeled drugs from four reference strains of Enterococcus faecalis and a strain of Enterococcus faecium and found that most strains pumped out norfloxacin and chloramphenicol. Efflux of tetracycline was detected only in certain strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 17 publications
1
16
0
1
Order By: Relevance
“…While the association between CR-VRE and quinolone use is more difficult to explain, it has been shown that exposure to quinolones may result in upregulation of efflux mechanisms that also confer resistance to chloramphenicol [16]. The identification of efflux pumps in enterococci that expel quinolones, chloramphenicol, and tetracycline [17], may help to explain the higher levels of tetracycline resistance noted in our CR-VRE isolates.…”
Section: Discussionmentioning
confidence: 85%
“…While the association between CR-VRE and quinolone use is more difficult to explain, it has been shown that exposure to quinolones may result in upregulation of efflux mechanisms that also confer resistance to chloramphenicol [16]. The identification of efflux pumps in enterococci that expel quinolones, chloramphenicol, and tetracycline [17], may help to explain the higher levels of tetracycline resistance noted in our CR-VRE isolates.…”
Section: Discussionmentioning
confidence: 85%
“…3 thus seems to block not only the NorA pump but also the additional MDR pumps14,15 in S. aureus . Furthermore 3 had excellent antibacterial activity (MIC 3.4 μM, Table 1) against E. faecalis which is known for its high levels of “intrinsic antibiotic resistance”16,17 and was resistant to 1 with an MIC of 650–1300 μM.…”
Section: Resultsmentioning
confidence: 99%
“…There is some homology ( Table 3) with proteins involved in cobalt transport [42^45], which in B. subtilis has been linked to tetracycline transport [46]. E. faecium possesses endogenous e¥ux pumps that excrete tetracycline [47]. Cobalt has been shown to activate an aminopeptidase in Streptococcus sanguis and Saccharomyces cerevisiae [48].…”
Section: Discussionmentioning
confidence: 99%
“…[20,21,23]. In E. faecium systems for enterocin A excretion [49] and antibiotic resistance [40,47] have been described. In E. faecalis an ABC transporter system has been implicated in polysaccharide biosynthesis [50].…”
Section: Discussionmentioning
confidence: 99%